Uncovering sarcopenia and frailty in older adults by using muscle ultrasound—A narrative review - Prell, Tino; Grimm, Alexander; Axer, Hubertus (Frontiers in Medicine, 2024)
Muscle ultrasound is a valuable non-invasive and cost-effective method in assessing muscle mass and structure, both of which are significant indicators for the development of sarcopenia and frailty in elderly individuals. Sarcopenia refers to the loss of muscle mass and strength that occurs with age, whereas frailty is a complex geriatric syndrome characterized by reduced physical function and an increased susceptibility to negative health outcomes. Both conditions are prevalent in older adults and are associated with higher risks of falls, disability, and mortality. By measuring muscle size and structure and several other ultrasound parameters, including muscle thickness, cross-sectional area, echogenicity (brightness in the ultrasound image), pennation angle, and fascicle length ultrasound can assist in identifying sarcopenia and frailty in older adults. In addition, ultrasound can be used to evaluate muscle function such as muscle contraction and stiffness, which may also be affected in sarcopenia and frailty. Therefore, muscle ultrasound could lead to better identification and tracking of sarcopenia and frailty. Such advancements could result in the implementation of earlier interventions to prevent or treat these conditions, resulting in an overall improvement in the health and quality of life of the elderly population. This scoping review describes the benefits and challenges when using ultra-sound for the evaluation of frailty and sarcopenia.